Need for training or already OnTracc? Development and psychometric properties of an online transcultural competence questionnaire among psychotherapists - Atzor, Marie-Christin; Piegenschke, Katharina; Christiansen, Hanna (Frontiers in Psychology, 2022)
The prevalence of mental disorders among people with migration experiences is high. Studies have shown that despite the increasing number of patients from different cultures requiring therapy, treating them is still a major challenge. Furthermore, professional training aimed at improving transcultural competence is rare, and psychometric instruments assessing transcultural competence require improvement. Accordingly, this study aimed to develop and evaluate an online transcultural competence questionnaire (OnTracc) to assess transcultural competence among psychotherapists. Based on extensive literature research and expert interviews, 38-self-report statements referring to aspects of transcultural therapy (e.g., skills, knowledge, and awareness) were compiled. In two studies, 306 psychotherapists completed the OnTracc questionnaire. The multicultural counseling inventory (MCI), personality factors (BFI-K), experience in transcultural therapy, and demographic data were assessed as control variables. The exploratory factor analysis (EFA) revealed a 3-factor structure. The reliability of the scale ranged from ω = 0.73 to 0.81. These scales demonstrated substantial convergent and discriminant validity with the BFI-K and MCI subscales. Factorial validity was confirmed through confirmatory factor analysis. This validated inventory is the first to assess transcultural competence in therapeutic settings in the German language. Further analysis of the factorial validity of the different samples is recommended. Given the increasing diversity in the therapeutic landscape, additional development could help close the gap between the evolving treatment demands of culturally diverse patients and the lack of consideration in mental health and education.